Identifying vulnerable older adults at risk for functional decline in cardiac care wards: time to shift the paradigm. Issue 1 (2nd January 2023) - Jeuris, Anthony; Van Grootven, Bastiaan; Geyskens, Lisa; Milisen, Koen; Flamaing, Johan; Deschodt, Mieke
ABSTRACT: Objective: To determine whether routine screening with the Flemish version of the Triage Risk Screening Tool (fTRST) is a valid approach to determine which patients on cardiac care wards are at risk for inhospital functional decline and would benefit from geriatric expertise consultation. Methods: A secondary data-analysis of the G-COACH before-cohort, describing patient profiles and routine care processes, in 189 older adults on two cardiac care wards in the University Hospitals Leuven between September 2016 and June 2017. Inhospital functional decline was defined as an increase of at least one point on the Katz Index of Activities of Daily Living or death between hospital admission and discharge. Results: Nine in 10 patients had at least one geriatric syndrome and one-third developed functional decline. Based on the fTRST proposed cut-off of ≥2, 156 (82.5%) patients were at risk for functional decline (sensitivity of 95.2%, specificity of 23.8%, negative predictive value of 90.9% and Area Under the Curve of 0.60). Of the 156 'at risk' patients, 43 (27.6%) received a consultation by the geriatric consultation team after a median of four hospitalization days. A positive fTRST was not significantly related to geriatric consultations (x 2 = 0.57; p = 0.45). Conclusion: The fTRST has a low discriminative value in identifying older cardiology patients at risk for functional decline. Given the high prevalence of geriatric syndromes, we propose a new paradigm were all older adults on cardiac care wards undergo a needs assessment upon hospital admission.